Efektivitas Sistem Penerimaan Siswa Baru Melalui Google Form di MI Muhammadiyah Romang Lompoa - Saenal, Saenal; Inganah , Siti (Jurnal Global Ilmiah, 2025)
This study aims to analyze the effectiveness of the new student admission system through Google Form at MI Muhammadiyah Romang Lompoa as an effort to digitize the administration of basic education. The background of this research is the need for educational institutions to increase efficiency and transparency in the process of admitting new students by utilizing digital technology. The research method used is qualitative descriptive with data collection techniques through observation, interviews, and documentation of teachers and school administrative staff. The results of the study show that the implementation of Google Forms is able to improve the efficiency of registration time, data processing accuracy, and user satisfaction. However, several obstacles were found, such as limited digital literacy of some parents and internet network disruptions. Overall, the new student admission system based on Google Form is considered effective and feasible to be developed as a digital administration model that supports educational transformation in the madrasah environment.